Triphenylamine Groups Improve Blocking Behavior of Phenoxazine Dyes in Cobalt‐Electrolyte‐Based Dye‐Sensitized Solar Cells. Issue 16 (14th August 2014) - Hao, Yan; Tian, Haining; Cong, Jiayan; Yang, Wenxing; Bora, Ilkay; Sun, Licheng; Boschloo, Gerrit; Hagfeldt, Anders
Abstract Novel phenoxazine dyes are successfully introduced as sensitizers into dye‐sensitized solar cells (DSCs) with cobalt‐based electrolyte. In sensitizers with triphenylamine (TPA) groups recombination from electrons in the TiO2 conduction band to the cobalt(III) species is suppressed. The effect of the steric properties of the phenoxazine sensitizers on the overall device performance and on recombination and regeneration processes is compared. Optimized DSCs sensitized with IB2 having two TPA groups in combination with tris(2, 2′‐bipyridyl) cobalt(II/III) yield efficiencies of 6.3 %, similar to that of IB3, which is equipped with mutiple alkoxy groups. TH310 with only one TPA group gives lower efficiency and open circuit voltage, while IB1 without TPA groups performs even worse. These results demonstrate that both TPA groups on the IB2 are needed for an efficient blocking effect. These results reveal a possible new role for TPA units in DSC sensitizer design.